Nonoperative Treatment of Elbow Ulnar Collateral Ligament Injuries With and Without Platelet-Rich Plasma in Professional Baseball Players: A Comparative and Matched Cohort Analysis. Issue 13 (November 2019) - Chauhan, Aakash; McQueen, Peter; Chalmers, Peter N.; Ciccotti, Michael G.; Camp, Christopher L.; D'Angelo, John; Potter, Hollis G.; Fealy, Stephen A.; Erickson, Brandon J.; Hoenecke, Heinz R.; Keefe, Daniel; McCauley, Julie; et al.
Background: Recent studies evaluating nonoperative treatment of elbow ulnar collateral ligament (UCL) injuries augmented with platelet-rich plasma (PRP) have shown promising results. To date, no comparative studies have been performed on professional baseball players who have undergone nonoperative treatment with or without PRP injections for UCL injuries. Hypothesis: Players who received PRP injections would have better outcomes than those who did not receive PRP. Study Design: Cohort study; Level of evidence, 3. Methods: The Major League Baseball (MLB) Health and Injury Tracking System identified 544 professional baseball players who were treated nonoperatively for elbow UCL injuries between 2011 and 2015. Of these, 133 received PRP injections (PRP group) before starting their nonoperative treatment program, and 411 did not (no-PRP group). Player outcomes and a Kaplan-Meier survival analysis were compared between groups. In addition, to reduce selection bias, a 1:1 matched comparison of the PRP group versus the no-PRP group was performed. Players were matched by age, position, throwing side, and league status: major (MLB) and minor (Minor League Baseball [MiLB]). A single radiologist with extensive experience in magnetic resonance imaging (MRI) interpretation of elbow injuries in elite athletes analyzed 243 MRI scans for which images were accessible for tear location and grade interpretation. Results: Nonoperative treatment of UCL injuries resulted in an overall 54% rate of return to play (RTP). Players who received PRP had a significantly longer delay in return to throwing ( P < .001) and RTP ( P = .012). The matched cohort analysis showed that MLB and MiLB pitchers in the no-PRP group had a significantly faster return to throwing ( P < .05) and the MiLB pitchers in the no-PRP group had a significantly faster RTP ( P = .045). The survival analysis did not reveal significant differences between groups over time. The use of PRP, MRI grade, and tear location were not statistically significant predictors for RTP or progression to surgery. Conclusion: In this retrospective matched comparison of MLB and MiLB pitchers and position players treated nonoperatively for a UCL tear, PRP did not improve RTP outcomes or ligament survivorship, although there was variability with respect to PRP preparations, injection protocols, time from injury to injection, and rehabilitation programs. MRI grade and tear location also did not significantly affect RTP outcomes or progression to surgery.